Cal. Polytechnic School Oct. '07 - Frank Aston::::::photographer::: (1907)
Faculty and student body of Cal Poly on steps of Weeks Administration Building, Oct. 1907. (1 addressed to Miss Mae Brew, signed 'G.A.J. Jr.'; 1 addressed to Miss Edith Bianchi, signed 'Joe,' (possibly Joseph Bianchi, Class of 1909); postmarked Oct. 24 1907; published in Polytechnic J. (v.3, no.1, Oct. 1907))